PENGARUH UKURAN PERUSAHAAN, FIXED ASSET INTENSITY, DAN LEVERAGE TERHADAP REVALUASI ASET TETAP PADA INDUSTRI FNB - Sihombing, Anita Indah Sari; Susanti, Merry (Media Mahardhika, 2024)
This study aims to analyze the impact of firm size, leverage, and fixed asset intensity on fixed asset revaluation in food and beverage companies listed on the Indonesian Stock Exchange from 2017 to 2021. Using a sample of 55 data points, the research employed Microsoft Excel for data management and IBM SPSS version 25 for statistical analysis. The results show that firm size and fixed asset intensity have no significant effect on fixed asset revaluation. However, leverage was found to have a significant positive influence on fixed asset revaluation, indicating that companies with higher leverage are more likely to revalue their fixed assets. This could be attributed to the need to improve their financial position or manage debt covenants. These findings offer insights into the financial strategies employed by firms and contribute to the understanding of factors that drive asset revaluation decisions, which are crucial for stakeholders evaluating a company's financial health and transparency